Latissimus dorsi flap for breast reconstruction - Zamora, Juan Carlos García (International Surgery Journal, 2025)
The latissimus dorsi flap (LDF) is a reliable and time-tested autologous option for breast reconstruction following mastectomy or breast-conserving surgery. It can be harvested as a myocutaneous or muscle-only flap, with or without fat grafting or implant placement, allowing tailored reconstruction based on patient anatomy, comorbidities, and aesthetic goals. The LDF is especially advantageous in patients who are not suitable candidates for abdominal-based free flaps or who present with compromised local tissues after radiation or failed reconstruction. Recent refinements, such as immediate fat augmentation and muscle-sparing techniques, have expanded its reconstructive versatility and improved donor-site outcomes. The most common complications are donor-site related, with seroma formation being the predominant issue, reported in up to 40% of cases. Other complications include hematoma, wound dehiscence, infection, and partial flap necrosis, though total flap loss is rare. Functional morbidity, particularly mild shoulder weakness or limited range of motion, may occur but generally has minimal impact on daily activities. Techniques preserving the thoracodorsal nerve and minimizing muscle harvest significantly reduce postoperative morbidity. Overall, the LDF provides consistent aesthetic and functional results, making it a valuable and versatile reconstructive option. Its safety, reliability, and adaptability-particularly when integrated with fat grafting-ensure its continued role in contemporary breast reconstruction.